Measuring the Effectiveness of Hypertension Education: Health Evaluation Study of A Village - Bujawati, Emmi; Jannah, Zahratul; Darmayanti, Firdha; Arfah, Nur Hasanah (Sociality: Journal of Public Health Service, 2024)
Hypertension is the leading cause of premature death worldwide with 1.28 billion adults affected, mostly in low- and middle-income countries. This community service program aims to assess the effectiveness of an extension program related to risk factors, screening, and the impact of hypertension conducted in Bontolebang Hamlet, Kec. Tombolo Pao, Kab. Gowa. This activity involved 30 households with a post-test questionnaire. Data were analyzed using the Fredman Test and showed a significant increase (p=0.000) in respondents’ knowledge of hypertension. The study results showed there was a difference in the mean score of knowledge level of hypertension counseling after 8 months of counseling. This study recommends that efforts should be made to increase access to health services for routine blood pressure measurement in the community to reduce the prevalence of hypertension in a sustainable manner.